Groundwater quality and depletion in the Indo-Gangetic Basin mapped from in situ observations - MacDonald, A.; Bonsor, H.; Ahmed, K.; Burgess, W.; Basharat, M.; Calow, R.; Dixit, A.; Foster, S.; Gopal, K.; Lapworth, D.; Lark, R.; Moench, M.; et al. (Nature Publishing Group, Macmillan Publishers Ltd, 2016)
Groundwater abstraction from the transboundary Indo-Gangetic Basin comprises 25% of global groundwater withdrawals, sustaining agricultural productivity in Pakistan, India, Nepal and Bangladesh. Recent interpretations of satellite gravity data indicate that current abstraction is unsustainable, yet these large-scale interpretations lack the spatio-temporal resolution required to govern groundwater effectively. Here we report new evidence from high-resolution in situ records of groundwater levels, abstraction and groundwater quality, which reveal that sustainable groundwater supplies are constrained more by extensive contamination than depletion. We estimate the volume of groundwater to 200 m depth to be >20 times the combined annual flow of the Indus, Brahmaputra and Ganges, and show the water table has been stable or rising across 70% of the aquifer between 2000 and 2012. Groundwater levels are falling in the remaining 30%, amounting to a net annual depletion of 8.0 ± 3.0 km3. Within 60% of the aquifer, access to potable groundwater is restricted by excessive salinity or arsenic. Recent groundwater depletion in northern India and Pakistan has occurred within a longer history of groundwater accumulation from extensive canal leakage. This basin-wide synthesis of in situ groundwater observations provides the spatial detail essential for policy development, and the historical context to help evaluate recent satellite gravity data.